From tetrapods to primates: conserved developmental mechanisms in diverging ecological adaptations. - Aboitiz, F; Montiel, J (2012)
Primates are endowed with a brain about twice the size that of a mammal with the same body size, and humans have the largest brain relative to body size of all animals. This increase in brain size may be related to the acquisition of higher cognitive skills that permitted more complex social interactions, the evolution of culture, and the eventual ability to manipulate the environment. Nevertheless, in its internal structure, the primate brain shares a very conserved design with other mammals, being covered by a six-layered neocortex that, although expands disproportionately to other brain components, it does so following relatively well-defined allometric trends. Thus, the most fundamental events generating the basic design of the primate and human brain took place before the appearance of the first primate-like animal. Presumably, the earliest mammals already displayed a brain morphology radically different from that of their ancestors and that of their sister group, the reptiles, being characterized by the presence of an incipient neocortex that underwent an explosive growth in subsequent mammal evolution. In this chapter, we propose an integrative hypothesis for the origin of the mammalian neocortex, by considering the developmental modifications, functional networks, and ecological adaptations involved in the generation of this structure during the cretaceous period. Subsequently, the expansion of the primate brain is proposed to have relied on the amplification of the same, or very similar, developmental mechanisms as those involved in its primary origins, even in different ecological settings.